2010
DOI: 10.1016/j.nurt.2009.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Damage: A Target for New Therapeutic Horizons

Abstract: Summary: Traumatic brain injury (TBI) represents a leading cause of death and morbidity, as well as a considerable social and economical burden in western countries, and has thus emerged as a formidable therapeutic challenge. Yet despite tremendous efforts enlightening the mechanisms of neuronal death, hopes for the "magic bullet" have been repeatedly deceived, and TBI management has remained focused on the control of increased intracranial pressure. Indeed, impairment of cerebral metabolism is traditionally a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 112 publications
0
14
0
Order By: Relevance
“…Mitochondrial proteins are considered to be potential therapeutic targets of many apoptosis-related diseases (Soustiel and Larisch 2010). Two main mitochondria proteins have been identified in mammalian cells, Smac/DIABLO and Omi/HtrA2 (Wilkinson et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondrial proteins are considered to be potential therapeutic targets of many apoptosis-related diseases (Soustiel and Larisch 2010). Two main mitochondria proteins have been identified in mammalian cells, Smac/DIABLO and Omi/HtrA2 (Wilkinson et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence shows that mitochondrial damage represents a crucial step toward delayed neuronal death following TBI, both as a target for multiple pathophysiological subcellular events, such as free radicals and calcium load, and as the source of activation of the so-called intrinsic apoptotic pathway (9)(10)(11). Despite the different nature and the origin of these mechanisms, most are characterized by permeabilization of the mitochondrial membrane (MMP) with subsequent dissipation of Δψ M and disruption of ATP production and may, therefore, represent a logical target for new therapeutic strategies (9,(11)(12)(13)(14). The 18 kDa translocator protein (TSPO), also known as peripheral-type benzodiazepine receptor, is a binding protein complex (15) located at the outer mitochondrial membrane and associated with two core components of the mPTP: the 32-kDa voltagedependent anion channel and the 30-kDa adenine nucleotide translocator (16).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been suggested that soy isoflavones, have scavenging function [40]. The disruption of BBB is also due to development of inflammatory mechanisms [41]. Anti-inflammatory effect of soy isoflavone has been demonstrated [42].…”
Section: Discussionmentioning
confidence: 99%